Active Participation in Dance and Liturgy : A Liturgical Dance Performance as Practice-as-Research - Vloebergs, Sander (Ex fonte, 2025)
This article explores the potential of liturgical dance as a form of theological inquiry through the case study OPUS CORPORIS, a choreographic intervention within the Catholic Eucharist. Developed as a practice-as-research project, the performance is analyzed as a hybrid form that reimagines the concept of active participation and challenges conventional boundaries between ritual and performance. Drawing on liturgical theology, performance studies, and contemporary dance, the article first situates the concept within historical developments in church and dance traditions. It then offers a close analysis of the performance, suggesting that it destabilizes normative liturgical scripts and provokes theological reflection – indicating that doubt, disruption, and improvisation are not obstacles to faith, but essential forms of participation. It highlights how such hybrid forms destabilize normative liturgical structures, provoke theological reflection, and invite renewed engagement with the sacred through embodied imagination.